Pengaruh lama kering kandang dan periode laktasi terhadap produksi dan kualitas susu awal laktasi pada sapi perah - Dian Wahyu Harjanti; Zahra Madhini Krismony; Rudy Hartanto (Universitas Sebelas Maret, 2021)
Objective: This study aims to determine the relationship between length of dry - and lactation period on milk production of early lactation, as well as milk fat, lactose, protein and specific gravity.Methods: A total of 24 dry period Friesian Holstein cows at the 7th month of pregnancy were used. The dry period length were divided into 4 groups and consists of 3 periods of lactation. Parameters determined were milk production and quality in the first month of lactation. Data were tested using the Kruskal Wallis for the effect of dry period length and lactation period on milk production and quality. Wilcoxon analysis for continued trials of significant results.Results: The results showed that 40-79 days dry period length had no significant effect on milk production (P= 0.854), milk specific gravity (P= 0.922), milk fat (P= 0.339), milk protein (P= 0.392) and milk lactose (P= 0.635). Lactation period has a significant effect on milk production (P= 0.001), milk fat (P= 0.011), milk protein (P= 0.028), milk lactose (P= 0.004), but has no significant effect on milk density (P= 0.683). The highest milk production was produced in the VI period with milk production at 675.17 liters/ month (P= 0.001).Conclusions: The dry period of 40 to 79 days gives similar milk production and quality. The lactation period affects the amount and quality of milk at early lactation. Lactating cows reared in good management are able to produce milk with good quality and high production until the-VI of lactation period.